Evaluasi Tingkat Kapabilitas Manajemen Permintaan dan Insiden Layanan (DSS02) Pada Badan Kepegawaian Daerah Kabupaten Lumajang Menggunakan Framework COBIT 5 - Achmad Andriansyah; Andi Reza Perdanakusuma; Ismiarta Aknuranda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Regional Personnel Agency (BKD) of Lumajang Regency as a government agency that an important role in the management of district civil servants, has several information technologies that support the services owned. As an organization that follows the development of information technology, it takes a management of information technology services to overcome the challenges of emerging threats and new risks that are likely to occur due to an IT incident (Daft & Marcic, 2006). Managers should be able to cope with IT incidents effectively and efficiently so as not to cause harm to the organization as IT decreases reputation. Given the importance of a management service and the role of managers as parties planning, organizing, leading, and controlling the resources of the Organization, the authors initiative to evaluate the implementation of the Service management in the institution of BKD Lumajang District uses the COBIT 5 framework on the DSS02 process (Request Management and service incident) because COBIT 5 is created by ISACA which is an organization that provides knowledge, certification, community and education on organizational Governance and IT management with regard to risk and IT compliance. The capability level result of the evaluation is at level 0 with a percentage of 41.5%. While the target capability level, which is Level 1 so there is a gap 1 level. The recommendation of improvement provided consists of 23 recommendations mapped to the roadmap with a span of 5 years.